[OP.8C.03] COMPARISON BETWEEN THREE NON-INVASIVE TECHNIQUES OF EVALUATION MICROVASCULAR MORPHOLOGY VS. THE GOLD-STANDARD LOCALLY INVASIVE MICROMYOGRAPHY. PRELIMINARY DATA. (September 2017) - De Ciuceis, C.; Caletti, S.; Coschignano, M.A.; Rossini, C.; Duse, S.; Docchio, F.; Pasinetti, S.; Zambonardi, F.; Semeraro, F.; Sansoni, G.; Rosei, C. Agabiti; Pileri, P.; et al.
Abstract : Objective: The evaluation of the morphological characteristics of small resistance arteries in human beings in not easy. The gold standard is generally considered to be the evaluation of the media to lumen ratio (M/L) of subcutaneous small vessels obtained by local biopsies and evaluated by wire or pressure micromyiography. However, non-invasive techniques for the evaluation of retinal arterioles were recently proposed, in particular two approaches seem to provide interesting information: scanning laser Doppler flowmetry (SLDF) and adaptive optics (AO); both of them provide an estimation of the wall to lumen ratio (WLR) of retinal arterioles. A non-invasive measurement of basal and total capillary density may be obtained by videomicroscopy/capillaroscopy. No direct comparison of the three non-invasive techniques in the same population was previously performed, in particular AO was never validated against micromyography. Design and method: In the present study we enrolled 12 normotensive subjects and 8 hypertensive patients undergoing an election surgical intervention; 11/20 were severely obese). All patients underwent a biopsy of subcutaneous fat during surgery. Subcutaneous small resistance artery structure was assessed by wire myography and the M/L was calculated. WLR of retinal arterioles was obtained by Scanning Laser Doppler Flowmetry and AO (SLDF, Heidelberg Engineering, Heidelberg, Germany and RTX-1, Imagine Eyes, Orsay, France). Functional (basal) and structural (total) microvascular density were evaluated by capillaroscopy (Videocap 3, DS Medica, Milan, Italy) before and after venous congestion. Results: The results are summarized in the Table (slope of the relation: p < 0.01 RTX-1 vs. SLDF). Figure. No caption available. Conclusions: Our data suggest that AO has a substantial advantage over SLDF in terms of evaluation of microvascular morphology, since it is more closely correlated with the M/L of subcutaneous small arteries, considered a gold-standard approach but limited in its clinical application by the local invasiveness of the procedure.